พฤติกรรมตามแนวคิดการบริโภคอย่างยั่งยืนของเกษตรกรในจังหวัดอุตรดิตถ์ต่อการซื้อรถใช้ในงานเกษตรกรรม - ปารวดี ไคร้ชม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Behavior according to sustainable consumption concept is the consumption behavior with the responsibilities to socio-economic and environmental impacts to sustain resources of products and services for the next generations. This study aimed to study the behavior according to sustainable consumption concept of farmers in Uttaradit province towards purchasing agricultural vehicles. Data were collected by the distribution of questionnaires to 360 samples from 9 districts in Uttaradit province, each of which was 40 samples. Data obtained were, then, analyzed by the descriptive statistics, including frequency, percentage, and mean, as well as the inferential statistics. The findings presented that there was an equal number of farmer respondents residing in Mueang, Luplae, Phichai, Tron, Thong Saen Khan, Tha Pla, Nam Pad, Fak Tha, and Ban Khok districts. Male respondents were found in the greater number than female respondents. The majority was in the age of 46-50 years old and their education background was lower than secondary school level. They mostly cultivated rice and earned an average of annual income at 100,001-300,000 Baht. They had had experience in using agricultural vehicles for more than 5 years; but not exceeding 15 years. Size of the riced-fields that they worked on was larger than 20 Rais; but not exceeding 50 Rais. Regarding the land procession authority, the respondents were the land owner who had all rights on land. Main reason of purchasing agricultural vehicle was to deliver agricultural products and the second reason was to carry agricultural tools and machineries. They owned one agricultural vehicle with 14-15 horsepower and with the capacity to carry the weight of 3-4 tons. They paid for it at lower than 160,000 Baht in installment terms. The money that they spent for the agricultural vehicle was the loan as approved by the Bank for Agriculture and Agricultural Co-operatives (BAAC) or the Agricultural Marketing Co-operative Limited (AMC), of which the down payment rate was less than 15%, and the interest rate was ranged between 6% - 10%. They chose to have an annual installment payment for the period of more than 5 years (over 60 terms of installment). They used the agricultural vehicle in July, which was the pre-cultivation period. Person influencing their purchasing decision was family members. They mostly purchased it at Sri Sa-nga Pattana Shop because this shop distributed the qualified products. The maintenance cost for the agricultural vehicle was around 501-1,500 Baht. In an overview, the factors namely product, price, place, and promotion affecting the purchase of agricultural vehicle were rated at high level of importance. In addition, the farmers agreed in neutral level towards impacts in three aspects: environmental, social, and economic. According to the study on behavior according to sustainable consumption concept, the results presented that in an overview, the respondents agreed with the sustainable consumption concept at 3.82 level. This study, then, divided the respondents into 2 groups. The first group was those who agreed with the sustainable consumption concept at the level of over than or equal to 3.82. The second group was those who were general consumers who agreed with the studied concept at the level at lower than 3.82. Hereafter were shown the top opinions towards behavior according to sustainable consumption concept that were agreed at the highest level: opinion on organizational behavior in socio-economic aspects, opinion on organizational behavior in environmental aspect, opinion on personal behavior in environmental aspect, and opinion on personal behavior in social aspect. The opinion on personal behavior in economic aspect was, however, rated at unsure level.